Low-temperature magnetic properties of deeply buried gas hydrate bearing sediments: a case study from IODP expedition 375 site U1519C in the Hikurangi subduction zone, New Zealand - Liu, Shixian; Li, Xuesen; Xu, Kunyu (Frontiers in Earth Science, 2025)
The diagenetic pathways, mineral types, and products of magnetic minerals in gas hydrate-bearing sediments are closely linked to burial depth. During IODP Expedition 375, drilling at the northern Hikurangi margin recovered 83.09 m of core from the gas hydrate stability zone (518.4–640.0 m depth) at Site U1519C. This provides an exceptional opportunity to investigate progressive diagenesis and fluid-driven late-stage diagenesis in deeply buried gas hydrate-bearing sediments. We conducted low-temperature magnetic measurements on 13 samples from this interval, including: (i) Low-temperature cycling (LTC) cycles, (ii) Zero-field-cooled (ZFC) and field-cooled (FC) curves, (iii) Low-temperature hysteresis loops, and (iv) Low-temperature alternating current (AC) magnetic susceptibility. Using features such as low-temperature transitions and curve trajectory patterns, we determined the types, concentrations, and assemblages of magnetic minerals, analyzed the origins of magnetic particles. Key results reveal: (1) Deeply buried sediments exhibit notably low SIRM intensity, indicating scarce magnetic minerals dominated by superparamagnetic (SP) and single-domain (SD) particles. This indicates that the deeply buried sediments experienced extensive pyritization under sustained reducing diagenetic conditions; (2)Despite the dominance of SP signals in the low-temperature FC/ZFC curves, the observation of the Verwey transition at ∼118 K—a characteristic low-temperature phase transition stemming from magnetite’s structural transformation—provides definitive evidence for the presence of trace magnetite even at such depths (>580 mbsf); (3) A double Verwey transition (∼106 K and ∼118 K) was observed in some samples, which indicates the coexistence of biogenic magnetite and nearly stoichiometric magnetite; (4) Authigenic Greigite (Fe3S4), an intermediate product of pyritization (FeS2), is detected. Some greigite likely exists as SP particles, while a low index of hysteresis parameters (DJH) indicates limited contributions from stable SD greigite among ferrimagnetic minerals.This study provides low-temperature magnetic evidence for diagenetic processes affecting magnetic minerals in deeply buried gas hydrate-bearing sediments. It reveals partial magnetite preservation, greigite formation and transformation, and ultimate pyritization, offering new insights into magnetic mineral evolution in such environments.